Difference of copy number variation in blood of patients with lung cancer. Issue 1 (March 2021) - Heo, Yeonjeong; Heo, Jeongwon; Han, Seon-sook; Kim, Woo Jin; Cheong, Hyun Sub; Hong, Yoonki
Background: Lung cancer is the leading cause of cancer-related deaths worldwide. Copy number variation (CNV) in several genetic regions correlate with cancer susceptibility. Hence, this study evaluated the association between CNV and non-small cell lung cancer (NSCLC) in the peripheral blood. Methods: Blood samples of 150 patients with NSCLC and 150 normal controls were obtained from a bioresource center (Seoul, Korea). Through an epigenome-wide analysis using the MethylationEPIC BeadChip method, we extracted CNVs by using an SVS8 software-supplied multivariate method. We compared CNV frequencies between the NSCLC and controls, and then performed stratification analyses according to smoking status. Results: We acquired 979 CNVs, with 582 and 967 copy-number gains and losses, respectively. We identified five nominally significant associations (ACOT1, NAA60, GSDMD, HLA-DPA1, and SLC35B3 genes). Among the current smokers, the NSCLC group had more CNV losses and gains at the GSDMD gene in chromosome 8 ( P =0.02) and at the ACOT1 gene in chromosome 14 ( P =0.03) than the control group. It also had more CNV losses at the NAA60 gene in chromosome 16 ( P =0.03) among non-smokers. In the NSCLC group, current smokers had more CNV gains and losses at the ACOT1 gene in chromosome 14 ( P =0.003) and at HLA-DPA1 gene in chromosome 6 ( P =0.02), respectively, than non-smokers. Conclusion: Five nominally significant associations were found between the NSCLC and CNVs. CNVs are associated with the mechanism of lung cancer development. However, the role of CNVs in lung cancer development needs further investigation.